The Relationship Between Cardio-Ankle Vascular Index and Left Atrial Phasic Function in Hypertensive Patients With Preserved Ejection Fraction - Tabata, Tsuyoshi; Shimizu, Kazuhiro; Morinaga, Yukihiro; Tanji, Naoaki; Yoshida, Ruiko; Iwakawa, Masahiro; Kiyokawa, Hajime; Takada, Nobuo (Frontiers in Medical Technology, 2021)
Background: To investigate the relationship between arterial stiffness, reflected by cardio-ankle vascular index (CAVI) value, and left atrial (LA) phasic function in hypertensive patients with preserved left ventricular ejection fraction (LVEF). Methods: We retrospectively studied 165 consecutive patients (mean age, 66.5 ± 11.7 years) diagnosed with hypertension with preserved LVEF who had undergone CAVI measurement and echocardiography on the same day. The latter included speckle-tracking echocardiography to assess LA phasic function (reservoir, conduit, and pump strain) and left ventricular global longitudinal strain (LVGLS). Results: The results of univariate analysis showed CAVI value to be correlated with LA reservoir strain and LA conduit strain (r = −0.387 and −0.448, respectively; both P < 0.0001). The results of multiple linear regression analysis showed CAVI value to be independently related to age (β = 0.241, P = 0.002) and LA conduit strain (β = −0.386, P = 0.021) but not LV mass index, LA volume index, or LV systolic function (including LVGLS). Conclusion: In hypertensive patients with preserved LVEF, increased CAVI value appears to be independently associated with impaired LA phasic function (particularly LA conduit function) before LA and LV remodeling. CAVI determination to assess arterial stiffness may be useful in the early detection of interactions between cardiovascular abnormalities in hypertensive patients.